The Effect of Dividend Policy on the Market Value of Firms in the Financial Services Sector in Nigeria - Ogbulu, Onyemachi Maxwell; Emeni, Francis Kehinde (Archives of Business Research, 2015)
The main thrust of this study is to find out the relationship between dividend policy and market value of firms in the financial services sector of the Nigerian economy. The study used panel data constructed from the financial statements of firms listed on the NSE for a period of 10 years, from 2002-2011. These financial statements were obtained from the NSE Fact Book. The Ordinary Least Square (OLS) statistical technique was used for the data analysis. From the results of the study, cash dividend, stock dividend and investment policy have a negative but not significant relationship with the market value of firms in the financial services sector of Nigeria, while earnings was found to have a positive and insignificant relationship with market value (though significant at 10% level of significance). Generally, the result is in tandem with the dividend irrelevant hypothesis, that dividend policy has no effect on market value of firms. Based on these results, some recommendations were made prominent amongst which was that companies operating in the financial services sector of Nigeria should not see dividend policy as a strategy towards increasing their market value and therefore, the dividend irrelevant hypothesis should not be jettisoned.